Neurofilament Light Regulates Axon Caliber, Synaptic Activity, and Organelle Trafficking in Cultured Human Motor Neurons - Sainio, Markus T.; Rasila, Tiina; Molchanova, Svetlana M.; Järvilehto, Julius; Torregrosa-Muñumer, Rubén; Harjuhaahto, Sandra; Pennonen, Jana; Huber, Nadine; Herukka, Sanna-Kaisa; Haapasalo, Annakaisa; Zetterberg, Henrik; Taira, Tomi; et al. (Frontiers in Cell and Developmental Biology, 2022)
Neurofilament light (NFL) is one of the proteins forming multimeric neuron-specific intermediate filaments, neurofilaments, which fill the axonal cytoplasm, establish caliber growth, and provide structural support. Dominant missense mutations and recessive nonsense mutations in the neurofilament light gene (NEFL) are among causes of Charcot-Marie-Tooth (CMT) neuropathy, which affects the peripheral nerves with the longest axons. We previously demonstrated that a neuropathy-causing homozygous nonsense mutation in NEFL led to the absence of NFL in patient-specific neurons. To understand the disease-causing mechanisms, we investigated here the functional effects of NFL loss in human motor neurons differentiated from inducible pluripotent stem cells (iPSC). We used genome editing to generate NEFL knockouts and compared them to patient-specific nonsense mutants and isogenic controls. iPSC lacking NFL differentiated efficiently into motor neurons, with normal axon growth and regrowth after mechanical axotomy, and contained neurofilaments. Electrophysiological analysis revealed that motor neurons without NFL fired spontaneous and evoked action potentials with similar characteristics as controls. However, we found that in the absence of NFL, human motor neurons 1) had reduced axonal caliber, 2) the amplitude of miniature excitatory post synaptic currents (mEPSC) was decreased, 3) neurofilament heavy (NFH) levels were reduced, and no compensatory increases in other filament subunits were observed, and 4) the movement of mitochondria, and to lesser extent lysosomes, was increased. Our findings elaborate the functional roles of NFL in human motor neurons. NFL is not only a structural protein forming neurofilaments and filling the axonal cytoplasm, but our study supports the role of NFL in the regulation of synaptic transmission and organelle trafficking. To rescue the NFL deficiency in the patient-specific nonsense mutant motor neurons we used three drugs, amlexanox, ataluren (PTC-124) and gentamicin to induce translational read through or inhibit nonsense mediated decay. However, the drugs failed to increase the amount of NFL protein to detectable levels and were toxic to iPSC-derived motor neurons.